The Effect of Sales Growth and Corporate Governance on Tax Avoidance with Company Size as a Moderating Variable - Yuliana Resca; Yanuar Ramadhan (International Journal of Social Service and Research, 2023)
The goals at this study is for decide impact sales growth, independent board of commissioners, the executor of the audit, also belongs to the institution at tax avoidance where company size is moderated. This studies design are quantitative. This energy uses the energy (mining) sector through purposive sampling. Researchers used a documentation strategy to obtain data from the 2019-2022 annual reports of industrial businesses. How to analyze data at this studies uses descriptive statistics, classical assumption tests also hypothesis test by utilizing the support of Microsoft Excel software and using statistical testing tools. Trade developments had an effect tax avoidance, while commissioner of independence, executor of audit, also institutional ownership have nothing impact tax avoidance. The acquisition in this research indicate that’s company size are able for moderate trade developments tax avoidance, company size are not abled for moderates the impact of independence committee, audit committee, also institutional ownership at tax avoidance. The acquisition at this research can serve as a basis for further study at sector of tax avoidance and corporate governance. These findings may trigger the development of new theories or enrich existing theories in relation to how certain factors influence corporate behavior regarding taxes. In this research, there are 1 figure, 5 tables with a total number of references of 32.